Cryolite glass prosthetic eyes—the response of the anophthalmic socket - Rokohl, Alexander C.; Adler, Werner; Koch, Konrad R.; Mor, Joel M.; Jia, Renbing; Trester, Marc; Pine, Nicola S.; Pine, Keith R.; Heindl, Ludwig M. (Graefes Archive For Clinical and Experimental Ophthalmology, 2019)
Purpose: To investigate mucoid discharge and the inflammatory response of anophthalmic sockets to cryolite glass prosthetic eye wear. Patients and methods: A total of 101 cryolite glass prosthetic eye wearers used visual analog scales (0–10) to measure frequency, color, volume, and viscosity of mucoid discharge associated with their prosthesis. Standardized photographs of the conjunctiva of their anophthalmic sockets were taken and conjunctival inflammation was semi-quantitatively graded (0–4). All characteristics of discharge and conjunctival inflammation were correlated to eye loss cause, hand washing behavior, and cleaning regimes as explanatory variables. Results: Mean mucoid discharge characteristics (0–10 scale) were frequency 5.3 ± 2.8, color 4.8 ± 3.2, volume 4.9 ± 3.0, and viscosity 5.1 ± 3.2. The mean conjunctival inflammation score (0–4 scale) was 2.1 ± 1.0. There was a positive correlation between the grade of conjunctival inflammation and the frequency (p = 0.018), color (p = 0.001), volume (p = 0.003), and the viscosity of mucoid discharge (p = 0.005). More conjunctival inflammation was associated with higher frequency of cleaning (p < 0.001) and lower frequency of hand washing before removal (p = 0.001). Higher frequency, color, volume, and viscosity of discharge were associated with higher frequency of cleaning (p ≤ 0.001). Conclusions: Discharge severity associated with prosthetic eye wear was positively correlated with more conjunctival inflammation, higher cleaning frequency, and less hand washing before handling. The results suggest that cryolite glass eyes should not be removed daily for cleaning and that further research should be undertaken to develop a standardized treatment protocol for managing inflammation and mucoid discharge. This protocol would advise hand washing before handling cryolite glass eyes and recommend a minimum period of wear between cleaning sessions.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Anophthalmic socket; Discharge; Enucleation; Eye loss; Ocular prostheses; Prosthetic eyes